Chaos Theory (IntechOpen, 2024)
Chaos Theory – Recent Advances, New Perspectives and Applications provides a comprehensive overview of chaos theory. It includes five chapters that discuss the history and development of chaos theory, the effectiveness of a chaos auto-associated model based on the Chebyshev-type activation function, neurite morphology, chemical self-replication, and the use of chaotic small particles to create materials with specific refractive index and magnetic permeability.